Analysis of Sharia and Conventional Monetary Policy Transmission in the SBY-Jokowi Era - Nabila Adenina Zidni Maulida; Slamet; Eko Suprayitno (Journal of Islamic Economics and Finance Studies, 2025)
This research is motivated by the role of monetary policy in the sustainability of a country's financial system, which is carried out through the transmission of monetary policy in order to achieve an output of economic stability. In Indonesia, the monetary policy transmission system is more complex due to the implementation of a dual financial system, consisting of conventional and sharia systems. In this study, the focus of the study is directed at the path of asset prices as a link between monetary policy, economic growth, and inflation. The main purpose of this study is to examine the short-term and long-term relationship between conventional monetary instruments (BI7DRR) and sharia (SukBI) on asset prices (JCI, SUN, JII, SBSN) as well as macroeconomic output by comparing the government systems of President Susilo Bambang Yudhoyono (2004–2014) and President Joko Widodo (2014–2024). The method used is causal-comparative design with a quantitative approach through the Vector Error Correction Model (VECM) model and the Chow test to determine the structural differences between the two governments. The results showed that there was a long-term cointegration relationship in the two systems, but the transmission patterns differed structurally between periods. The conventional system affects inflation faster, while the Islamic system shows a long-term influence on economic growth. These findings confirm the need to optimize sharia instruments in maintaining national macroeconomic stability.   Penelitian ini dilatarbelakangi oleh peran kebijakan moneter dalam keberlangsungan system keuangan suatu negara, yang dilakukan melalui transmisi kebijakan moneter agar tercapat suatu output kestabilan ekonomi. Di Indonesia system transmisis kebijakan moneter lebih kompleks karena diterapkannya sistem keuangan ganda, yang terdiri atas sistem konvensional dan syariah. Dalam Penelitian ini Fokus kajian diarahkan pada jalur harga aset sebagai penghubung antara kebijakan moneter, pertumbuhan ekonomi, dan inflasi. Tujuan utama penelitian ini adalah menguji hubungan jangka pendek dan jangka panjang antara instrumen moneter konvensional (BI7DRR) dan syariah (SukBI) terhadap harga aset (IHSG, SUN, JII, SBSN) serta output makroekonomi dengan mengkomparasi sistem pemerintahan Presiden Susilo Bambang Yudhoyono (2004–2014) dan Presiden Joko Widodo (2014–2024). Metode yang digunakan adalah causal-comparative design dengan pendekatan kuantitatif melalui model Vector Error Correction Model (VECM) dan uji Chow untuk mengetahui perbedaan struktur antar kedua pemerintahan. Hasil menunjukkan adanya hubungan kointegrasi jangka panjang pada kedua sistem, namun pola transmisi berbeda secara struktural antarperiode. sistem konvensional lebih cepat memengaruhi inflasi, sementara system syariah menunjukkan pengaruh jangka panjang terhadap pertumbuhan ekonomk. Temuan ini menegaskan perlunya optimalisasi instrumen syariah dalam menjaga stabilitas makroekonomi nasional.